Single-cell RNA sequencing advances in revealing the development and progression of MASH: the identifications and interactions of non-parenchymal cells - Ning, Meng; Lu, Donghui; Liang, Dong; Ren, Pei-Gen (Frontiers in Molecular Biosciences, 2025)
Developing drugs for the treatment of Metabolic Associated Steatohepatitis (MASH) has always been a significant challenge. Researchers have been dedicated to exploring drugs and therapeutic strategies to alleviate disease progression, but treatments remain limited. This is partly due to the complexity of the pathophysiological processes, and inadequate knowledge of the cellular and molecular mechanisms in MASH. Especially, the liver non-parenchymal cells (NPCs) like Kupffer cells, hepatic stellate cells and sinusoidal endothelial cells which play critical roles in live function, immune responses, fibrosis and disease progression. Deciphering how these cells function in MASH, would help understand the pathophysiological processes and find potential drug targets. In recent years, new technologies have been developed for single-cell transcriptomic sequencing, making cell-specific transcriptome profiling a reality in healthy and diseased livers. In this review, we discussed how the use of single-cell transcriptomic sequencing provided us with an in-depth understanding of the heterogeneous, cellular interactions among non-parenchymal cells and tried to highlight recent discoveries in MASH by this technology. It is hoped that the summarized features and markers of various subclusters in this review could provide a technical reference for further experiments and a theoretical basis for clinical applications.